Lentivirus-Carried microRNA-195 Rescues Memory Deficits of Alzheimer’s Disease Transgenic Mouse by Attenuating the Generation of Amyloid Plaques - Su, Dan; Chai, Yani; Yang, Junkai; Wang, Xuqiao; Liu, Ying; Ma, Jing; Tang, Xin; Mishra, Chandan; Chandra, Shah Ram; Yue, Weidong; Ai, Jing (Frontiers in Pharmacology, 2021)
Although lots of new drugs are developed to treat Alzheimer's disease (AD), many clinical trials of monotherapy have failed to affect disease progression or symptoms compared with placebo. Recently, scientists believe that combination treatment is more necessary than monotherapy. A series of previous studies reported that microRNA-195 (miR-195) can improve the declined cognitive function of ApoE4(+/+) mice and rats suffering from chronic brain hypoperfusion (CBH) by targeting multi-genes that related to AD pathology, including amyloid precursor protein (APP) and β-site APP cleaving enzyme 1 (BACE1) genes.However, whether the gain-of-function of miR-195 could improve the impaired learning and memory ability of APP/PS1 transgenic mouse has not been reported. In this study, we administered lentivirus-carried miR-195 to 4-month-old (4M) APP/PS1 mice by stereotaxic injecting into bilateral hippocampi. After treatment for 1M, 2M and 3M, the cognitive effect of miR-195 were evaluated by Morris water maze (MWM) test. Western blot was used to detect the expression of APP, BACE1 and AT8.Aβ plagues were quantitatively assessed by immunofluorescence technique. We found that the declined cognitive phenotype of APP/PS1 mice occurred at the age of 6M, not at the age of 5M. And treatment of Lv-pre-miR-195 to APP/PS1 mice for 1M did not achieve any changes. Although Lv-pre-miR-195 treatment for 2M improved the declined learning ability of APP/PS1 mice, it did not affect the memory functions. However, treatment with Lv-pre-miR-195 for 3M can effectively improve both the learning and memory ability of APP/PS1 mice at the age of 7M. Further studies demonstrated that gain-of-function of miR-195 by Lv-pre-miR-195 injection could inhibit the increased APP and AT8 expression of APP/PS1 mice but did not affect BACE1 level that was not changed in both hippocampus and cortex. By counting the number of Aβ plaques of different sizes we found that Lv-pre-miR-195 treatment mainly reduced the number of Aβ plaques of less than 20μm, but did not affect the number of Aβ plaques of greater than 50μm. Taken together, the gain-of -function of miR-195 in the hippocampus can improve the cognition of APP/PS1 mice by inhibiting the generation of new plaques rather than affecting the already formed ones.